Implementation of Coaching Method in Improving Students' Leadership Style at Abu Syafa Modern Islamic Boarding School - Yohana, Yohana; Hasibuan, Rabitah Hanum (Lembaga Riset Mutiara Akbar, 2025)
The problem in this study focuses on the fact that many students are still inactive and lack confidence in leadership. This is due to the use of conventional teaching methods and minimal guidance. The study aims to analyze the implementation of coaching to improve students' leadership styles at Pondok Pesantren Modern Abu Syafa Binjai and to evaluate its impact on the development of their leadership skills. This research uses a qualitative method with a descriptive approach. Data were collected through observation, interviews, and documentation. The results show that the coaching method is effective in enhancing students' confidence, critical thinking, and independence in decision-making. Previously passive students became more proactive in pesantren organizations. Key factors influencing the success of coaching include student motivation, mental readiness, and the coach’s communication and guidance skills.